Uji Mesin Crusher Brondolan Sawit dengan Mata Potong Circular Saw Standar - Adhe Anggry; Subkhan Subkhan (Politeknik Manufaktur Negeri Bangka Belitung, 2019)
Palm brondolan are the outer fruit of the loose bunches and fall to the ground. Palm brondolan is used as a feed ingredient. Processing of palm brondolan for feed ingredients needs to be done by the process of damaging the material structure. This study aims to determine the quality of palm brondolan crusher using standard cutting eyes and determine the right shaft. In this study the crusher machine was designed using 13 circular cutting eyes to see the standard ? 4? x 1.75 mm, the number of teeth 40 pieces and the distance between cutting eyes 5 mm. This machine uses a source of driving power in the form of a 3 phase electric motor with 3 HP power and has a rotating speed of 1420 rpm and a rotation ratio of 1: 1 shaft. This study uses the experimental method, by comparing the shaft test with the quality of the palm blended crusher. The quality characteristics that are addressed are the smaller the better. The results of the study, obtained an effective engine capacity of 30 kg/hour. The quality of the crusher at 700 rpm shaft speed accelerated the size of coir length from 1 to 30 mm and the volume of shell and seed granules 8-27 mm3 while in shaft rotation 1420 rpm the size of 1-20 mm coir and the volume of grain and seeds 4-12 mm3 were obtained. From the results of the experiment proving that circular cutting eyes see the standard capable of destroying palm leaflets and shaft rotation affect the quality of the crusher. The 1420 rpm shaft rotation has a better crusher quality compared to 700 rpm shaft rotation.